Implementasi Algoritma Knuth-Morris-Pratt pada Perancangan Aplikasi Chatbot Kamus Istilah Komputer Berbasis Web - Arif Iik Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The search process in the computer term dictionary will be very helpful for anyone who wants to know a computer term, but the search process is slow and time-consuming where it makes it difficult for users because they have to search for terms manually by opening each page one by one. A large number of dictionary pages, from alphabet A to alphabet Z. To speed up and simplify the search process, an algorithm is needed to maximize the search process. In this study, we will implement the knuth-morris-pratt algorithm in the design of a web-based computer term dictionary chatbot application using a system development model, namely the waterfall model. The results of this study are in the form of a web-based computer term dictionary chatbot application, with the existence of this chatbot application the search for a computer term becomes faster and more efficient.